Accompagner un changement de fonction à partir d'un dispositif réflexif : l'analyse de pratiques comme lieu d'émergence d'un « genre professionnel » ? - Thérèse Pérez-Roux (Université de Provence, 2015)
The article is interested in the transition from a function towards another supported by a device from accompaniment set up for new actors from education: the teacher-referents (TR) for the Adjustment to school and the Schooling of the Handicapped pupils (ASH). The theoretical framework privileges a sociological entry on the dynamic identity ones, combined with an approach by "clinic of activity". 15 TR were followed over four years (2010-2013). The results put forward many tensions. Beyond the emotional distance to which asks the institution, the TR evoke the impact of the relational dimension of their activity. The device of accompaniment is perceived by these actors like a help with the transition and the occasion to build with pars on the basis of emblematic situations (shared) the premises of a "professional genre".